Keeping the peace: An investigation of the interaction between personality, conflict, and competence on organizational citizenship behaviors. Issue 2 (6th May 2014) - L. Kisamore, Jennifer; W. Liguori, Eric; Muldoon, Jeffrey; Jawahar, I.M.
Abstract : Purpose: – The purpose of this paper is to investigate the interaction between self-reported proactive personality, competence, and interpersonal conflict in the prediction of supervisor ratings of organizational citizenship behaviors directed at individuals (OCBI) and organizations (OCBO). Design/methodology/approach: – Data were obtained from 165 full-time subordinate-supervisor dyads. Employees self-reported personality and control variable information in wave 1 and competence and interpersonal conflict information in wave 2. Data regarding employee OCB performance were collected from supervisors in wave 3. Findings: – Results suggest that OCBs are performed less frequently in stressful circumstances but that proactive personality appears to assuage the effects of stress. Significant two- and three-way interactions suggest the interplay of personal and situational characteristics are more complex in predicting OCBO than OCBI, likely due to its more distal nature. Practical implications: – Results of the current study suggest steps managers may want to take to increase employee performance of OCBs, specifically, selecting proactive individuals, creating training programs to bolster employees' competence, and minimizing interpersonal conflict at work. Originality/value: – The current study confirms and extends extant research. The current study goes beyond previous work to consider a more complex interaction of factors that are related to employee engagement in OCBs.